The Effect of Profitability, Leverage, Firm Size, and Sales Growth on Firm Value - Agustar, Gryara Anrasia; Nilawati, Yuana Jatu (Jurnal MANDIRI: Ilmu Pengetahuan, Seni, dan Teknologi, 2025)
Research purposes this study aims to analyze the effect of profitability, leverage, firm size, and sales growth on firm value in Food and Beverage sector companies listed on the Indonesia Stock Exchange (IDX) during 2021–2023. Method/Approach The research sample consisted of 37 companies with a total of 111 observations. Data were analyzed using panel data regression with the Random Effect Model (REM) approach, selected based on the results of the Chow, Hausman, and Lagrange Multiplier tests. Research Results The results indicate that profitability (ROA) has a significant positive effect on firm value, leverage (DER) has a significant negative effect on firm value, while firm size and sales growth also have significant positive effects on firm value. Conclusion this study implies the importance for companies to manage leverage prudently and to enhance profitability, business scale, and sales growth in order to increase firm value.